PENERAPAN GAYA MENGAJAR LATIHAN TERHADAP HASIL BELAJAR LOMPAT JAUH PADA SISWA KELAS X - Badar Sallam, - (2019)
Badar Sallam (2019). Implementation of teaching Practice style on student learning outcomes in long jump learning (class action research on TGB students of Class X 1 SMKN 1 Cirebon) Supervisor I: Dr. Yudy Hendrayana, M. Kes, AIFO. Supervisor II: Dr. H. Dian Budiana, M. Pd. The study aims to test the field of teaching practice style implementation to improve student learning outcomes in remote jump learning. The method used is class action research. The subject of this study is all students of Class X TGB SMKN 1 Cirebon which amounted to 32 people's. The instrument used is the observation sheet of student activity. The results of the analysis and calculation of test data of the skills at the time of the observation were estimated at 29.88%, Cycle 1 by 47.25%, and cycle 2 by 88.86%. The study was chopped up to 2 cycles due to significant improvements. It is thus inferred that the implementation of the Teaching practice style can improve student learning outcomes for long jump learning for students X TGB 1 SMKN 1 Cirebon. Keywords: teaching practice style, long jump, learning outcomes.